PENGARUH KEMAH BLOK TERHADAP SIKAP KEDISIPLINAN SISWA KELAS XI DI SMK FARMASI IKASARI PEKANBARU - Muhamad Gunawan; Jumili Arianto; Indra Primahardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the Block Model which is 1 of 3 models in implementing mandatory scouting in schools. This model must be carried out once a year for all students. In general, schools more often carry out extramural or outdoor block-style activities, better known as block camps. However, it is quite sad that there is no research or evaluation of the implementation of this system, which should require a control in order to assess whether the block camp system can still be relevant to be implemented or routinely carried out every year, especially in improving disciplinary attitudes for students so that researchers want to take a role and become an angler as proof and evaluation of the implementation of the block camp. This research method uses quantitative methods with a statistical approach. The data collection instrument used in this research was a questionnaire consisting of 29 statement items. The population in this study was 278 people and the sample taken in this study was 25% of the total population to 69 informants, namely class XI using the Proportional Random Sampling Technique. Based on the results of research on the influence of block camp on the discipline of class XI at the Ikasari Pharmacy Vocational School, Pekanbaru, it can be concluded that: There is an influence of block camp on the discipline of class XI students at the Ikasari Pharmacy Vocational School, Pekanbaru.